(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The proposed system presents the design of a surveillance system for emergency patient transport. India has the highest number of road accidents in the world, so this system will help you monitor the location of ambulances using Google Maps and GPS. To prevent this, it is possible to provide medical facilities to accident victims in a short time with the help of advanced wireless GPS technology. Continuous monitoring of ambulance location and patient condition during critical times of patient transport can help improve medical care. One of the problems in patient transport is transportation related issues. Therefore, high-speed, economical and efficient traffic control is required. You can view the location of the ambulance and the patient’s heart rate and temperature status. After receiving the SMS, the hospital can prepare staff for the correct treatment of the next patient. The proposed system tracks the route of an incoming ambulance and turns all traffic lights in the same lane green after an ambulance is detected. The proposed system also preserves the patient’s previous prescribing information and contributes to better treatment. Patient data can be obtained using biometric devices available in ambulances.